Survey on the Use of Whole-Genome Sequencing for Infectious Diseases Surveillance: Rapid Expansion of European National Capacities, 2015–2016 - Revez, Joana; Espinosa, Laura; Albiger, Barbara; Leitmeyer, Katrin Claire; Struelens, Marc Jean; , ECDC National Microbiology Focal Points; Experts Group; Tóth, Ákos; Griškevičius, Algirdas; Vatopoulos, Alkiviadis; Skoczynska, Anna; Pantosti, Annalisa; et al. (Frontiers in Public Health, 2017)
Whole Genome Sequencing (WGS) has become an essential tool for public health surveillance and molecular epidemiology of infectious diseases and antimicrobial drug resistance. It provides precise geographical delineation of spread and enables incidence monitoring of pathogens at genotype level. Coupled with epidemiological and environmental investigations it delivers ultimate resolution for tracing sources of epidemic infections. To ascertain the level of implementation of WGS-based typing for national public health surveillance and investigation of prioritised diseases in the European Union (EU)/European Economic Area (EEA), two surveys were conducted in 2015 and 2016. The surveys were designed to determine the national public health reference laboratories’ access to WGS and operational WGS-based typing capacity for national surveillance of selected foodborne pathogens, antimicrobial resistant pathogens and vaccine-preventable diseases identified as priorities for European genomic surveillance. Twenty-eight and twenty-nine out of the 30 EU/EEA countries participated in the survey in 2015 and 2016, respectively. National public health reference laboratories in 22 and 25 countries had access to WGS-based typing for public health applications in 2015 and 2016, respectively. Reported reasons for limited or no access were lack of funding, staff and expertise. Illumina technology was the most frequently used followed by Ion Torrent technology. The access to bioinformatics expertise and competence for routine WGS data analysis was limited. By mid-2016, half of the EU/EEA countries were using WGS analysis either as first- or second-line typing method for surveillance of the pathogens and antibiotic resistance issues identified as EU priorities. The sampling frame as well as bioinformatics analysis varied by pathogen/resistance issue and country. Core genome multilocus allelic profiling, also called cgMLST, was the most frequently used annotation approach for typing bacterial genomes suggesting potential bioinformatics pipeline compatibility. Further capacity for WGS-based typing is developing in many countries and upon consolidation and harmonisation of methods should enable pan-EU data exchange for genomic surveillance in the medium term subject to the development of suitable data management systems and appropriate agreements for data sharing